Stability Analysis of Slopes Under Seismic Action with Asynchronous Discounting of Strength Parameters - Ruipeng Wang; Hongye Yan; Junkai Yao; Zhuqing Li (Applied Sciences)
A non-proportional reduction in strength parameters is widely used in slope stability assessment, but the current asynchronous reduction in strength parameters only considers the cohesion c and internal friction angle φ, which is suitable for slope stability assessment under static loads. Under seismic loads, however, tension at the rear edge of the slope often accompanies the appearance of ground cracks. In order to consider the relationship between tensile strength, cohesion, and the internal friction angle reduction coefficient, starting with the linear softening attenuation law of soil material strength parameters, a functional relationship between cohesion and internal friction angle is obtained. Then, considering that the failure of microelements in the tensile and shear zones conforms to the tension and shear of joint failure, the relationship between tensile strength, cohesion, and the internal friction angle reduction coefficient is derived. By establishing a homogeneous slope model and comparing and analyzing the progressive instability failure modes of slopes under static and seismic conditions, the stability and potential slip surface differences of slopes under two different working conditions are explored. The research results indicate that slope instability is a gradual, cumulative failure process under both static and dynamic conditions. The instability mode of the slope under static conditions is shear failure. In contrast, under dynamic loads, the instability failure of the slope is manifested as shear failure upward at the foot of the slope and tensile failure downward at the top of the slope. The stability coefficient of slopes under earthquake conditions is reduced by 17.3% compared to that under static conditions. Under earthquake conditions, the potential sliding surface under an asynchronous reduction in strength parameters is shallower than that under static conditions and deeper than that without an asynchronous reduction in strength parameters. Overall, the research results provide a reference for slope stability analysis and support design optimization under earthquake loads.